Application of biomass leachate in regulating the fusibility of coal ash. (15th May 2020) - Wang, Jiajian; Liu, Xia; Guo, Qinghua; Wei, Juntao; Chen, Xueli; Yu, Guangsuo
Graphical abstract: Highlights: Application of biomass leachate in regulating fusibility of coal ash was studied. Biomass leachate has a stronger ability in decreasing AFTs of SA coal than biomass. RS leachate has greater influence on the ash fusibility of coal than CS leachate. By adding biomass leachate, low low-melting leucite and eutectic formed. Abstract: Biomass leachate was rich in water-soluble alkali and alkali earth metals (AAEM) species, which can effectively reduce the ash fusion temperatures (AFTs) of coal ash. In this study, a high silicon-aluminium coal (SA) with high AFTs and typical agricultural biomasses were selected to investigate the application of biomass leachate in regulating the fusibility of coal ash. The results showed that with the addition of biomass leachate, the AFTs of high silicon-aluminium coal with high-melting temperatures could be effectively reduced by greater than 70 °C, and the effect of biomass leachate on reducing the AFTs of coal ash is stronger than that of biomass. The ash chemical composition of the biomass alone could not fully reflect the ability of biomass leachate in regulating the fusibility of coal ash, the content of water-soluble AAEM and the evaporation of alkali metal elements in ashing process also had a significant influence. By adding biomass or biomass leachate into the SA, low-melting leucite and gehlenite, which would react with anorthite to generate low-melting eutectic, formed, resulting in the remarkable decrease of AFTs of SA. Exothermic peak temperature (EPT) and flow temperature (FT) showed an approximate linear relationship as FT ≈ EPT + 65 °C. The prediction results of FactSage were basically correspond to the experimental results.